Enjoyment the moral significance of styles of life - Kekes, John. (Oxford : Clarendon, 2008)
John Kekes examines the indispensable role enjoyment plays in a good life. The key to it is developing a style of life that combines an attitude and a manner of living and acting that jointly express one's deepest concerns.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Pleasure; Joy; Life